2020
DOI: 10.1155/2020/9324689
|View full text |Cite
|
Sign up to set email alerts
|

A Novel 3D Reconstruction Algorithm of Motion-Blurred CT Image

Abstract: The majority of medical workers are eager to obtain realistic and real-time CT 3D reconstruction results. However, autonomous or involuntary motion of patients can cause blurring of CT images. For the 3D reconstruction scene of motion-blurred CT image, this paper consists of two parts: firstly, a GAN image translation network deblurring algorithm is proposed to remove blurred results. This algorithm adopts the clear image to supervise the training process of the blurred image, which creates solutions that are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 27 publications
1
3
0
Order By: Relevance
“…It suggested that the median method had good feasibility in the MC algorithm. This is basically consistent with the research results of a new 3D reconstruction algorithm for motion-blurred CT images [ 15 ]. The research by Ibáñez et al [ 16 ] (2021) showed that the MC algorithm had a good application effect in imaging technology, which provided support for the credibility of this research.…”
Section: Discussionsupporting
confidence: 91%
“…It suggested that the median method had good feasibility in the MC algorithm. This is basically consistent with the research results of a new 3D reconstruction algorithm for motion-blurred CT images [ 15 ]. The research by Ibáñez et al [ 16 ] (2021) showed that the MC algorithm had a good application effect in imaging technology, which provided support for the credibility of this research.…”
Section: Discussionsupporting
confidence: 91%
“…Introducing intelligent algorithm into CT imaging can greatly improve the sharpness of image [ 16 ]. Jing et al [ 17 ] can clearly supervise the training process of fuzzy images by using 3D reconstructed CT images, and the intelligent algorithm used showed good results. Huang et al [ 18 ] used intelligent algorithm to ensure the quality of CT image registration and obtain the accuracy of dual-energy images.…”
Section: Discussionmentioning
confidence: 99%
“…Computed tomography (CT) is crucial in medical diagnosis and illness analysis [1][2][3][4][5]. As excessive CT scan probably causes a series of acute potential cancers and cases, the medical instrument usually adopts a CT radiation dose as low as possible to avert the damage to health.…”
Section: Introductionmentioning
confidence: 99%